Corporate taxation and investment: Explaining investment dynamics with firm-level panel data - Nadja Dwenger (Arbeitskreis Quantitative Steuerlehre (arqus), 2009)
Using a firm-level panel data set I assess whether dynamic models of investment provide an empirically fruitful framework for analyzing tax effects on changes in capital stock. In particular I estimate a one-step error correction model (ECM) complementing the usual estimation of a distributed lag model. A correction term accounts for non-random sample attrition, which has not been considered in previous studies on investment even though most (if not all) panel data sets on firms are incomplete. Both, ECM and distributed lag model, suggest that user cost of capital and output have an economically and statistically significant influence on capital formation. In the ECM, however, estimates are larger in size and match theoretical predictions more closely. My preferred estimate of -1.3 implies that a decrease in the user cost of capital by 10 percent will increase the firm's capital stock by 13 percent, on average. Taking my elasticity estimate to the Corporate Tax Reform 2008 I would expect that the reform only slightly increases capital stock, since the rather strong reduction in corporate income tax rate was partly compensated for by stricter depreciation allowances. Investment dynamics appear to be crucial for the coefficients of cash flow variables in investment equations. While cash flow effects are present in the (firstdifferenced) distributed lag model, they vanish in the ECM. This leads me to conclude that well documented cash flow effects point at dynamic misspecification in previous studies.
Keywords: E22; H25; H32; 330; Taxation; Business investment; User cost of capital; Dynamic specification; Körperschaftsteuer; Steuerwirkung; Investition; Kapitalkosten; Statistik der Unternehmen und Arbeitsstätten; Panel; Fehlerkorrekturmodell; Schätzung; Deutschland